Impression Laundering of Le Minerale: A Directional Branded Content Analysis - Deddy Setiawan; Firdia Pradita Ramadhanti; Irine Shafana Jasmine; Mala Ismawati; Miftahul Ocha Awalia; Moehammad Hary Wibisono; Marina Sinar Lestari (Jobmark: Journal of Branding and Marketing Communication, 2024)
Competition in the bottled mineral water market has created a brand communication war between brands, including Le Minerale. Through various advertisements and digital communications on social media, Le Minerale tries to fend off various adverse claims made by competitors regarding single-use gallon packaging products. This article dissects the communication content of the Le Minerale brand from the perspective of Wijaya's Impression Laundering theory using the directional Branded Content Analysis (BCA) method. The findings show that Le Minerale uses various content strategies, both visual, verbal, and audiovisual, to launch dramaturgical and angelic communication strategies, as explained in the theory of impression laundering. This study is helpful as a critical reflection, both for brands and audiences, in understanding the modes of impression laundering in brand communication.